Dynamic changes of lipid profile in Romanian patients with Gaucher disease type 1 under enzyme replacement therapy: a prospective study. Issue 3 (14th September 2012) - Zimmermann, Anca; Grigorescu‐Sido, Paula; Rossmann, Heidi; Lackner, Karl J.; Drugan, Cristina; Al Khzouz, Camelia; Bucerzan, Simona; Naşcu, Ioana; Zimmermann, Tim; Leucuţa, Daniel; Weber, Matthias M.
Abstract: Background: Dyslipidemia in Gaucher disease includes reduced total, low‐density lipoprotein (LDL)‐, and high‐density lipoprotein (HDL)‐cholesterol (C). No prospective analysis of lipid profile changes in treatment‐naïve patients under enzyme replacement therapy (ERT) is available. Methods: We analyzed lipid profile changes during ERT in a prospective controlled manner. Twelve treatment‐naïve patients, Gaucher disease type 1 (GD1), 29.5 ± 12.9 years, 4M/8F. Diagnosis was made by enzymatic measurement and mutational analysis. Total‐, LDL‐, and HDL‐C, triglycerides (TG), and LDL subfractions were assessed before the start of ERT with imiglucerase and biannually for 3 years. Patients were matched with healthy controls before and after 3 years of ERT. Results: At baseline, we found severely reduced HDL‐C concentrations (23.6 ± 5.4 mg/dl) and enhanced LDL/HDL ratios (3.1 ± 0.7). HDL‐C increased after 6 months (29.2 ± 5.7, p = 0.023), LDL/HDL ratio decreased after 30 months (2.5 ± 0.5, p = 0.039). TG, even not consistently enhanced at baseline (128 ± 31.3 mg/dl), yet higher than in controls ( p < 0.001), decreased after 18 months, being comparable with controls after 3 years of ERT. Small, dense LDL (mg/dl) increased continuously without significant difference to controls. After 3 years of ERT, only reduced HDL‐C concentrations persisted as a potentially atherogenic alteration; however, mean concentrations markedly improved (42.9 ± 8.3 mg/dl, p < 0.001). Lipid parameters correlated with six markers of disease severity. Conclusions: This is the first prospective controlled study regarding lipid profile dynamics during ERT (glucocerebrosidase) in initially treatment‐naïve GD1 patients. The most important changes were reduced HDL‐C and enhanced LDL/HDL ratio. Their dynamics during ERT and correlations with markers of disease activity suggest that they can be considered markers of disease severity and follow‐up in Gaucher patients under treatment.